Pengaruh Motivasi Guru Terhadap Hasil Belajar Matematika Materi Pecahan Pada Siswa Kelas IV Ssekolah Dasar Inpres 109 Perumnas Kota Sorong - Yakobus Bwarnirun; Budi Santoso (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This study aims to determine the effect of teacher motivation on mathematics learning outcomes in fractional material in class IV SD Inpres 109 Perumnas Sorong City. This research is an experimental study using a pretest-posttest group design research design. The independent variable in this study is teacher motivation while the dependent variable is learning outcomes. The sample of this study was the 50th-grade students of SD Inpres 109 Perumnas Sorong City as many as 50 students, divided into two groups namely the Experimental Group with 25 students and the Control Group with 25 students. Data collection techniques used were questionnaire, test, observation, and documentation. The data analysis technique consists of three stages, namely the stage of a description of the data, the stage of testing the requirements of the analysis, and the stage of testing the hypothesis. Questionnaire reliability test results obtained Cronbach's Alpha results of 0.860. Then the reliability test results of the pre-test results obtained Cronbach's Alpha results of 0.750 and the reliability test of the post-test questions obtained Cronbach’s Alpha results of 1.258. From the analysis of the results of the calculation of the motivation of learning experimental class students obtained a total score of 1787 with an average of 3.574. Percentage of 64% shows good motivation from students and 36% shows quite a good category. Whereas the control class obtained a total score of 1748 with an average of 3.496. Percentage of 64% shows good motivation from students and 36% shows quite good category. From the data analysis, the Kolmogrov Smirnov Asymp normality test was obtained. Sig (2-tailed)> 0.05 then normal data is obtained. From the analysis of the data obtained homogeneity test that Asymp. Sig (2-tailed)> 0.05 then obtained homogeneous data. Paired T-test results obtained the t value of the experimental class t count of 14.334 while the t class of the control class of 14.511 and the value of t count> t table or sig 0.000 <0.05 in both classes then H1 is accepted and H0 is rejected. So it can be concluded that there is an influence of teacher motivation on learning outcomes of fraction material mathematics in class IV SD Inpres 109 Perumnas Sorong City, if the teacher's negative expectations decrease, the learning achievement of students will increase